The structure of Leguminosae-Detarioideae dominant rain forest in Korup National Park, Cameroon - van der Burgt, Xander M.; Newbery, David M.; Njibili, Sylvanos (Plant ecology and evolution, 2021)
Background and aims - We studied a cluster of trees in the Leguminosae subfamily Detarioideae, to: (1) determine the size, structure, and tree species composition of this cluster; (2) map the size, shape, and structure of groups of individual Detarioideae tree species in the cluster. Location - Lowland rain forest in southern Korup National Park, in the Southwest Region of Cameroon. Material and methods - Trees in permanent plots were recorded using standard plot enumeration techniques. Outside plots, single-species tree groups were recorded by a rapid technique. From this data, detailed maps of groups of trees were prepared. Key results - Detarioideae tree species occur co-dominant in a cluster of at least 32 km2 with an irregular shape. The cluster contained at least 42 Detarioideae tree species; at least 29 of these occurred in groups ranging in size from 50 to 4000 m across, depending on the species. Groups usually had circular shapes, caused by ballistic seed dispersal. In a group, trees were always mixed with trees of several other Detarioideae species. Every area within the cluster contained a specific set of Detarioideae species. The percentage of Detarioideae trees ≥ 60 cm stem diameter on 50 ha was up to 76% in Detarioideae-rich forest, to 6% in Detarioideae-poor forest. Of all trees in the centre of the cluster, 2.8% belonged to pioneer forest species, which indicates that disturbance levels were low during the past generations of trees. Discussion - The forests in the Detarioideae cluster have not been subject to substantial human and natural impacts in historic or prehistoric times. Such forests are exceptional in Africa. Detarioideae clusters may indicate glacial age forest refuges, especially clusters that contain both many different Detarioideae species and some Detarioideae species endemic to the cluster.